Research Outside The Academy Professional Knowledge-Making in the Digital Age - Börjesson, Lisa.; Huvila, Isto.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book analyses the practical, information-related dimensions of professional knowledge making and communication in extra-academic organisations. It treats the sites where research takes place and where knowledge is created outside academia in the light, among other things, of new digital resources. It provides valuable insight into the practices through which extra-academic research data and results are produced and made available and the settings in which this takes place. With case studies of knowledge-making in government organizations and state research institutes, as well as in cultural and heritage institutions, this book broadens the perspective on knowledge sharing, communication and publication, and how knowing changes as a result of the professional knowledge-making practices in the digital age. Research outside the Academy is ideal for students at all levels looking for an introduction to the topic of research and knowledge-making insociety. Moreover, researchers and professionals in the fields of library and information science and science and technology studies will find the book to be adding to previous understandings of scholarly documentation and communication.
Chapter 1 Introduction -- Chapter 2 Environmental Research and Knowledge Production within Governmental Organizations -- Chapter 3 Making and Publishing Knowledge in Research Institutes -- Chapter 4 Making Knowledge Work: the Function of Public Knowledge Organisations in the Netherlands -- Chapter 5 Librarians Conducting Library Research: What is Happening outside the Academy -- Chapter 6 Contract Archaeology -- Chapter 7 Knowledge-Making in Business Organizations -- Chapter 8 Grey Literature and Professional Knowledge Making -- Chapter 9 How Knowing Changes -- Chapter 10 Epilogue.
Keywords: Sociology -- Methodology; Communication; Knowledge, Sociology of; Educational technology; Education and state; Sociological Methods; Media and Communication; Sociology of Knowledge and Discourse; Digital Education and Educational Technology; Education Policy